Pion, kaon, and proton production in central Pb-pb collisions at √sNN=2.76 TeV - Abelev, Betty; Busch, Oliver; Engel, Heiko; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lara Martinez, Camilo Ernesto; Lohner, Daniel; Mercado Pérez, Jorge; Oyama, Ken; et al. (Physical review letters, 2012)
In this Letter we report the first results on π±, K±, p, and ¯p production at midrapidity (|y|<0.5) in central Pb-Pb collisions at √sNN=2.76 TeV, measured by the ALICE experiment at the LHC. The pT distributions and yields are compared to previous results at √sNN=200 GeV and expectations from hydrodynamic and thermal models. The spectral shapes indicate a strong increase of the radial flow velocity with √sNN, which in hydrodynamic models is expected as a consequence of the increasing particle density. While the K/π ratio is in line with predictions from the thermal model, the p/π ratio is found to be lower by a factor of about 1.5. This deviation from thermal model expectations is still to be understood.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
B. Abelev, O. Busch, H. Engel, P. Glässel, R. Grajcarek, N. Herrmann, T. Krawutschke, M.J. Kweon, C. Lara, D. Lohner, J. Mercado Pérez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, K. Schweda, J. Stachel, J. Ulrich, S. Vallero, J. Wiechula, B. Windelband, P. Zelnicek, A. Zimmermann [und weitere]
Gesehen am 30.11.2018